1995
DOI: 10.1021/bi00036a002
|View full text |Cite
|
Sign up to set email alerts
|

Proximity Mapping the Surface of a Membrane Protein Using an Artificial Protease: Demonstration That the Quinone-Binding Domain of Subunit I Is near the N-Terminal Region of Subunit II of Cytochrome bd

Abstract: A novel experiment has been used to show proximity relationships between sites on the surface of the cytochrome bd quinol oxidase of Escherichia coli. The artificial protease iron (S)-1-[p-(bromoacetamido)benzyl]-EDTA (Fe--BABE) was conjugated to selected reactive cysteines placed in subunit I or subunit II, with the aim of identifying amino acid residues within approximately 12 A of each site of attachment. The protease was activated with H2O2 and ascorbate for a few seconds, and hydrolysis products were isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 44 publications
0
39
0
Order By: Relevance
“…Alternatively, short living hydroxyl radicals can abstract a hydrogen from the ␣-carbon of an amino acid leading to an unstable carbon-centered radical that degrades, forming new blocked termini (18). In both cases, the cleavage is limited to a 1.2-nm distance from the attachment site of the chemical protease (29,30). The cleavage is very fast and achieved within 10 s (see Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, short living hydroxyl radicals can abstract a hydrogen from the ␣-carbon of an amino acid leading to an unstable carbon-centered radical that degrades, forming new blocked termini (18). In both cases, the cleavage is limited to a 1.2-nm distance from the attachment site of the chemical protease (29,30). The cleavage is very fast and achieved within 10 s (see Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The different mutations observed indicate that the different isolates were, for the most part, the result of independent events. All but two of the observed mutations in the cydA product appeared to be located in the portion of the protein found in the periplasmic space (16,17,22), and considering the stop codons observed, it is likely that the mutations inactivated the enzyme. The wildtype cydA ϩ gene was able to complement the suppressed strain to restore filamentous killing.…”
Section: ϫ6mentioning
confidence: 97%
“…The former group includes most of the c-proteobacteria, while the latter group includes all of the Gram-positive bacteria, the cyanobacterium, and the c-proteobacterium Pseudomonas aeruginosa (Osborne and Gennis 1999;Sakamoto et al 1999). It has been demonstrated that the Q-loop is adjacent to loop I-II in subunit II (Ghaim et al 1995). Furthermore, the Q-loop is known to be involved in quinol binding (Ghaim et al 1995).…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that the Q-loop is adjacent to loop I-II in subunit II (Ghaim et al 1995). Furthermore, the Q-loop is known to be involved in quinol binding (Ghaim et al 1995). The cytochrome bd complex contains three prosthetic groups: heme b 558 , heme b 595 , and heme d. Heme b 558 and heme b 595 are protoporphyrin, while heme d is a chlorin (Timkovich et al 1985).…”
Section: Introductionmentioning
confidence: 99%